HUBUNGAN TINGKAT RELIGIUSITAS DENGAN TIPE KEPRIBADIAN MANTAN PSK DESA BAMBANG WAJAK MALANG - Nurhayati Nurhayati (Jurnal Penelitian Ilmiah INTAJ, 2023)
This study aims to determine the relationship between the level of religiosity and the personality type of former prostitutes in Bambang village. This research uses quantitative methods. The sample of this study consisted of 10 former prostitutes who were determined by means of sampling using purposive sampling considering the specific criteria to be sampled, namely former prostitutes who are easy to talk to and socialize with. The research instrument used was a scale consisting of a religiosity scale and a Big Five personality type scale. Testing of the research instrument was carried out using SPSS for Windows version 22. The results showed that the Cramer's V correlation value was 0.935 with a significance value of 0.025. Because the significance value obtained is less than the significant level of 0.05, it can be concluded that there is a significant relationship between the level of religiosity and the big five personality types. This means that there is a tendency for personality types with a level of religiosity. Like the Neuroticism personality type tends to have a high level of religiosity. Someone with this personality type tends to have a high sense of anxiety so they are afraid to commit a sin.